MEMORY ENHANCING EFFECT OF ANISE (PIMPINELLA ANISUM) WITH RESPECT TO ITS ANTIOXIDANT ACTIVITY IN ALBINO MICE - A. Mushtaq; R. Anwar; M. Ahmad (Journal of Animal and Plant Sciences, 2019)
The study was conducted to explore memory enhancing effect of Anise (Pimpinella anisum) to substantiate the scientific basis of its traditional use as a neurotic remedy. Aqueous (aqP.a) and n-hexane (nhP.a) fractions of crude Anise extracts were 1st investigated for phytochemical and antioxidant analysis and then administered to mice for behavioral (by using elevated plus maze (EPM), light dark test and hole board paradigms) and biochemical investigations. Flavonoids, tannins and phenols were found to be 127.43 ± 1.94, 201.04 ± 1.57 and 209.83 ± 1.30 mg/g, respectively for aqP.a and 125.33 ± 2.18, 74.66 ± 1.20 and 42.87 ± 1.65 mg/g, respectively for nhP.a. Values of IC50 were recorded as 37.48 and 166.53 µg/ml for aqP.a and nhP.a respectively. Moreover, aqP.a significantly (P < 0.001) improved inflexion ratios in EPM test and biochemical parameters like glutathiones, catalases and superoxide dismutases. The levels of acetylcholinesterase (AChE) and malondialdehyde (MDA) were significantly (P < 0.001) reduced by aqP.a as compared to nhP.a. The findings thus suggested that only aqueous extract of Anise improves memory both by preventing oxidative stress and by providing neuro protection to cholinergic pathways against AChE.
Keywords: Antioxidant; AChE; MDA; Dementia; Anise